2005
DOI: 10.1366/0003702055012591
|View full text |Cite
|
Sign up to set email alerts
|

Transmittance Fourier Transform Infrared Spectra of Liquid Water in the Whole Mid-Infrared Region: Temperature Dependence and Structural Analysis

Abstract: Transmittance Fourier transform infrared (FT-IR) spectra of liquid water in the 4-80 degrees C temperature range are reported in the whole mid-infrared (MIR) region (4000-360 cm (-1)). The spectra were recorded by using a newly developed, home-made transmittance cell, working in light vacuum conditions (pressures of the order of 3-4 millibar). This permits the elimination of the aqueous vapor bands from the liquid spectra, particularly in the bending region, and the rapid collection of data without fluxing lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
87
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(97 citation statements)
references
References 29 publications
10
87
0
Order By: Relevance
“…8 has been decomposed into the four contributions labelled as I i (i = 1, 4) corresponding to the different populations of OH oscillators present in the system. [50][51][52] As shown in previous studies, [36][37][38]40 the sums of the percentage intensities of the two sub-bands found, respectively, at the lowest and highest wavenumbers, i.e. (I 1 + I 2 ) and (I 3 + I 4 ) in Fig.…”
Section: Restructuring Of the Hb Network Of Confined Watersupporting
confidence: 79%
“…8 has been decomposed into the four contributions labelled as I i (i = 1, 4) corresponding to the different populations of OH oscillators present in the system. [50][51][52] As shown in previous studies, [36][37][38]40 the sums of the percentage intensities of the two sub-bands found, respectively, at the lowest and highest wavenumbers, i.e. (I 1 + I 2 ) and (I 3 + I 4 ) in Fig.…”
Section: Restructuring Of the Hb Network Of Confined Watersupporting
confidence: 79%
“…Infrared (IR) absorption spectra were recorded between 800 and 4000 cm −1 with an IFS28 Bruker spectrometer (resolution of 2 cm −1 ), using a cell with CaF 2 windows and without a spacer 25…”
Section: Methodsmentioning
confidence: 99%
“…Transmission spectra were collected at various temperatures, in the 295-365 K range, using a specially designed cell with CaF 2 windows [26]. Temperature of the experiment was controlled through a circulating water bath (Haake F6 ultra-thermostat), with a precision of 0.1K.…”
Section: Ftir Spectramentioning
confidence: 99%